1999
DOI: 10.2307/3285821
|View full text |Cite
|
Sign up to set email alerts
|

A Field Trial of the Effectiveness of a Feline Toxoplasma gondii Vaccine in Reducing T. gondii Exposure for Swine

Abstract: A 3-yr field trial was conducted on 8 commercial swine farms in Illinois to determine the effectiveness of a feline Toxoplasma gondii vaccine in reducing the exposure of swine to T. gondii. A vaccine consisting of live bradyzoites of the mutant T-263 strain, capable of preventing oocyst shedding by cats, was used in this study. Each farm was visited 3 times in 1994, 3 times in 1995, and once in 1996. Cats were trapped and inoculated with the T-263 oral vaccine during 1994 and 1995. On each visit, the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 17 publications
3
48
0
2
Order By: Relevance
“…Furthermore, it may be used for the assessment of drugs used to prevent oocyst shedding by T. gondii -infected cats 40 or for monitoring the effectiveness of potential vaccines that would limit oocyst shedding in cats. 41 The results of the present study demonstrate the sensitivity, consistency, and infective-stage specificity of the copro-PCR. When combined with the previously demonstrated test sensitivity and specificity, 27 it can be concluded that the copro-PCR is at least as sensitive, consistent, and infective stage-specific as the bioassay.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, it may be used for the assessment of drugs used to prevent oocyst shedding by T. gondii -infected cats 40 or for monitoring the effectiveness of potential vaccines that would limit oocyst shedding in cats. 41 The results of the present study demonstrate the sensitivity, consistency, and infective-stage specificity of the copro-PCR. When combined with the previously demonstrated test sensitivity and specificity, 27 it can be concluded that the copro-PCR is at least as sensitive, consistent, and infective stage-specific as the bioassay.…”
Section: Discussionmentioning
confidence: 62%
“…Toxoplasma gondii isolates from previously reported studies but not genetically characterised 2.1.1. Toxoplasma gondii isolates from rodents and cats from pig farms in Illinois, USA During the course of studies to determine sources of T. gondii infection on pig farms (Dubey et al, 1995), and methods to prevent T. gondii infection (Mateus-Pinilla et al, 1999), feral rodents and cats on these farms were examined for T. gondii infection. A decade later, some of these isolates were revived for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The potential of this vaccine in the field was tested in a large scale trial conducted on young cats caught and trapped on eight commercial pig farms in the USA. The cats were vaccinated with the T-263 vaccine and the efficacy of the vaccine was measured indirectly by examining seroprevalence of other intermediate animal hosts, including the farmed pigs within the study farms (Mateus-Pinilla et al 1999). The results showed a decrease in seroprevalence within the pig population implying that vaccinating the cats had reduced the shedding of T. gondii oocysts into the environment and therefore reduced the source of infectious material for the intermediate animal hosts in this area (Mateus-Pinilla et al 1999).…”
Section: Vaccines To Reduce Oocyst Sheddingmentioning
confidence: 99%